Bamboo based agroforestry for higher income and livelihood security of farmers and rural poor - Ahlawat, S. P. (Indian Farming, 2015)
Bamboo under agroforestry systems is suitable for intercropping,soil conservation, wind break, repaires filter and permaculture.They can be planted by farmers in homestead. small scale farmlands or managed as groves. Besides, bamboo can be grown with multipurpose tree species on wastelands or degraded lands.Bamboo based agroforestry gives much higher returns than the other systems.